EVOLUTION OF KNOWLEDGE DEVELOPMENT IN HUMAN RESUSCITATION - O. Zabolotina (Union of pediatricians of Russia, 2010)
Study of human resuscitation development history is the first step in understanding modern approaches to cardiopulmonary resuscitation. A significant increase in survival parameters is driven by accumulation of knowledge, expertise, improvement in resuscitation technologies. Development of cardiopulmonary resuscitation structure, development of recommendations approved for study and practical use, addressing these issues at the state level are accompanied with a significant reduction in mortality both at the hospital and pre-hospital levels. Key words: children, cardiopulmonary resuscitation, development stages, training of pediatricians. (Pediatric Pharmacology. - 2010; 7(3):25-27)